2023
DOI: 10.1126/sciadv.add4333
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling identifies ACE + granuloma macrophages as a nonpermissive niche for intracellular bacteria during persistent Salmonella infection

Abstract: Macrophages mediate key antimicrobial responses against intracellular bacterial pathogens, such as Salmonella enterica . Yet, they can also act as a permissive niche for these pathogens to persist in infected tissues within granulomas, which are immunological structures composed of macrophages and other immune cells. We apply single-cell transcriptomics to investigate macrophage functional diversity during persistent S. enterica serovar Typhimurium ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The complex cellular structure of granuloma is thought to be important for bacterial persistence. Recently, using single-cell transcriptomics, Pham et al identified diverse macrophage populations within Salmonella Typhimurium-induced granulomas ( Pham et al, 2023 ). In the present study, Salmonella persisted within aggregates of tnfa -negative macrophages that remind early granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…The complex cellular structure of granuloma is thought to be important for bacterial persistence. Recently, using single-cell transcriptomics, Pham et al identified diverse macrophage populations within Salmonella Typhimurium-induced granulomas ( Pham et al, 2023 ). In the present study, Salmonella persisted within aggregates of tnfa -negative macrophages that remind early granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…The complex cellular structure of granuloma is thought to be important for bacterial persistence. Recently, using single cell transcriptomics, Pham and collaborators identified divers macrophage populations within Salmonella Typhimurium induced granulomas 58 . In this study, Salmonella persisted within aggregates of tnfanegative macrophages that remind early granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Most human diseases originate from infections by various microbial bacteria. The representative drug of the organic class dominates the treatment of bacterial diseases, but there is antibiotic resistance during treatment process. Organic drugs such as penicillin, artemisinin, aspirin, , and valium have been widely used in the treatment of various diseases. The functional group , and conformational relationships of organic drugs play a key role for development of these drugs.…”
Section: Introductionmentioning
confidence: 99%